150th Anniversary of global adenoid investigations: unanswered questions and unsolved problems - Zwierz, Aleksander; Masna, Krystyna; Domagalski, Krzysztof; Burduk, Paweł (Frontiers in Pediatrics, 2023)
Although the problem of adenoid hypertrophy (AH) has been diagnosed and treated by doctors and scientists from around the world for the last 150 years, there is still no consensus regarding appropriate diagnosis, conservative treatment options, and qualification for surgery. This manuscript presents current knowledge on these issues and compares diagnostic methods and the effectiveness of treatment options. Factors that may influence the obtained treatment results are also described, and a questionnaire is proposed to compare the results of treatment. The objective of drawing attention to this problem is to obtain better results from conservative treatment in the future and better-qualified patients for surgical treatment.